MASSIVE INVASION OF RESILIENT EXOTIC FISHES IN THE RIVER GANGA: A CASE STUDY AT ALLAHABAD STRETCH - JOSHI, K D; Jha, D N; Alam, M A; Das, S CS; SRIVASTAVA, S K; KUMAR, VIJAY (Journal of the Inland Fisheries Society of India, 2020)
The Ganga is the fifth largest river in the world, which drains about 1,060,000 km2 geographical areas (Welcomme, 1985) in India and neighbouring countries. The river traverses through varied catchments consisting glacial no-vegetation zone, alpine and broad leaved forests, meadows, agricultural fields, high density human settlements and industrial developments. The altitudinal and geographical variation, vast and varied catchments, vegetation cover, substratum and influx ofnumerous tributaries of the river have given rise to varying substratum conditions and micro-habitats in the river. As a result, the river system is reported to harbor about fish 265 species (Sinha, 2006) including coldwater, warm water and estuarine fishes.